Thoracic Insufficiency Syndrome: Current Concept Review - Hogue, Grant; Emans, John (Journal of the Pediatric Orthopaedic Society of North America, 2021)
Thoracic insufficiency syndrome (TIS) is defined as an inability of the thorax to support normal respiration and lung growth. The majority of alveolar development occurs in the first 5 years of life and thus, this is a time of early vulnerability for the population with spine and chest wall differences. Rapid growth during this phase of life can quickly worsen chest and spine deformity. Advances have been made in the care of these patients with the orthopaedic focus on increasing thoracic volume to allow space for continued lung growth and development. Clinicians can group TIS patients based on their diagnoses but also the type of volume-depletion deformity (VDD) of their thorax. In doing this, there are guidelines for treatment and overall prognosis. Medical and surgical treatment options are constantly evolving and will ultimately be informed by obtaining accurate and reproducible pulmonary function data in the future.